Adaptive Impedance Controller for a Robot Astronaut to Climb Stably in a Space Station. (4th May 2016) - Wei, Bo; Jiang, Zhihong; Li, Hui; Dong, Que; Ni, Wencheng; Huang, Qiang
Maintaining stability is a significant challenge during the control of a robot astronaut while climbing with human-like dual-arm action in a space station. This challenge is caused by conflicting force generated by dynamic internal forces in the closed chain during dual-arm climbing. In general, an impedance controller is suitable for solving this problem. However, the conflicting force in the rigid closed chain is stored in the virtual spring of the impedance controller (especially in microgravity), where even small disturbances cause a significant change in robot astronaut movements. As such, it is difficult to select suitable control parameters for the stable climbing of a robot astronaut. This paper proposes an adaptive algorithm to optimize the impedance controller parameters. This eliminates conflicting force disturbances, with one arm in compliance with the motion of the other. It provides scope for achieving stable motion without the need for precise control parameters. Finally, the stability of the proposed algorithm is demonstrated by Lyapunov theory using a robot called ASTROBOT. The experimental results show the validity of the proposed algorithm.